2020
DOI: 10.1126/sciadv.abc3207
|View full text |Cite
|
Sign up to set email alerts
|

A 3D culture platform enables development of zinc-binding prodrugs for targeted proliferation of β cells

Abstract: Advances in treating β cell loss include islet replacement therapies or increasing cell proliferation rate in type 1 and type 2 diabetes, respectively. We propose developing multiple proliferation-inducing prodrugs that target high concentration of zinc ions in β cells. Unfortunately, typical two-dimensional (2D) cell cultures do not mimic in vivo conditions, displaying a markedly lowered zinc content, while 3D culture systems are laborious and expensive. Therefore, we developed the Disque Platform (DP)—a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…GSIS. The analysis was conducted following previously described procedure (48). The ceMEDs were loaded 150 μL of MIN6 cells or SC-βCs at a seeding density with 3 million cells or 2,000 IEQ.…”
Section: Methodsmentioning
confidence: 99%
“…GSIS. The analysis was conducted following previously described procedure (48). The ceMEDs were loaded 150 μL of MIN6 cells or SC-βCs at a seeding density with 3 million cells or 2,000 IEQ.…”
Section: Methodsmentioning
confidence: 99%
“…3(a) ]. 46 The developed DP included core extracellular matrix (ECM) components such as laminin and collagen type IV that are involved in human islet development. Consequently, they observed higher expression rates of key transcription factors (e.g., PDX1 and NKX6.1) and junctional structures (e.g., E-cadherin and connexin 36) in the 3D reconstituted beta cells inside the DP compared to 2D monolayer conditions.…”
Section: Modeling Dm Using Hierarchical 3d Constructsmentioning
confidence: 99%
“…Screening primary human b-cells for mitogens that had been previously identified to initiate proliferation in rodent b-cells revealed that many factors were unable to initiate significant replication, with the dual-specificity tyrosine phosphorylation regulated kinase 1A (DYRK1A)-inhibiting compound harmine being the only mitogen that induced significantly increased replication with treatment (31). Indeed, harmine is unique in that it has been repeatedly reported in the literature to induce bcell and other pancreatic cell replication (32)(33)(34)(35)(36)(37). Differing effects on b-cell replication through shared signaling mechanisms between rodent and human b-cells may be due to additional cellular factors that inhibit proliferation, such as the high accumulation of p16 in adult human b-cells (38)(39)(40).…”
Section: Comparison Of B-cell Proliferation Between Rodents and Humansmentioning
confidence: 99%
“…With this tool, it is possible to screen for chemical or genetic regulators that provide control over proliferation in pancreatic cells. In addition to using compound-based treatments previously mentioned, such as harmine (34,35,37), another method for inducing replication could be through viral delivery of controllable systems (70)(71)(72). Once proliferative drivers have been identified, rigorous examination of the expanded population must confirm that no aberrant mutations have been acquired during the process and that expanded cells retain the ability to form b-like cells.…”
Section: Potential Strategies and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation